Environmental project management methodology - Sholarin, E.; Awange, Joseph (2015)
© 2015, Springer International Publishing Switzerland. Project management is a set of tools and templates designed to help the project management practitioner and to provide consistency of process.It is a methodology that defines the processes, responsibilities, and workflows needed to achieve an objective.Each project or initiative undertaken is unique in its constraints and issues.The information contained within the methodology should be adapted to a particular situation.Based on this premise, Project Management Body of Knowledge (PMBoK) and Projects IN Controlled Environment, version 2 (PRINCE 2) should not be considered as a methodology, but rather as a guide, which should be tailored to suit organisation’s own internal project management methodology.